The Perception Reality of Sustainable Investment in Millennial and Generation Z - Lestari, Dini; Wiryono, Sudarso Kaderi (International Research Journal of Business Studies, 2023)
Extensive research on human behavior and decision-making has been conducted because sustainable practices are among the elements that help improve the quality of human life today. Members of various generations act differently from others in terms of consumer references, ideas, habits, and how they approach societal issues when making judgments. In addition to determining whether or not they are persuaded to adopt specific investing niches, like sustainable investments, based on their personal perspectives, the research aims to ascertain the level of awareness of sustainability issues in finance among Millennials and Generation Z in Indonesia. The research is presented as quantitative research, with 240 individual investor samples. Data were examined using structural equation modeling (SEM). The results indicate that influencers do not impact sustainable investment, while impact on return, risk-averseness, and positive performance positively influence sustainable investments. Finally, this paper discusses the implications for investors and the government.